Analisis Penerapan Program 5m Pada Pelaksanaan Ptm Terbatas di Masa Pandemi Covid-19 SDN 2 Nglangitan - Nafa Adliya; Yohana Setiawan (Peneliti.net, 2022)
This research includes evaluation research with Goal Free Evaluation model. This article is based on interviews, observations, and documentation studies. The subjects of this study were the principal, teachers and students in grades 1,2,3. In qualitative research, validity and reliability include credibility test, dependability test, confirmability test, and transfermability test. From the results of the study, it was shown that SDN 2 Nglangitan had planned prior to the implementation of limited PTM by implementing the 5M program. One of the implementations carried out by the school is holding a socialization about the importance of 5M. With this socialization, the principal hopes that school residents are more aware of the importance of health protocols. From the implementation of socialization, school residents are more aware of the importance of health protocols. This can be seen from educators, teaching staff and students who comply with the 5M health protocol. Research can be a reference regarding the implementation of the 5M program in limited PTM during the pandemic, especially in elementary schools.